The Role of Nahdlatul Ulama in Fostering Interfaith Harmony Through Social Capital in Palembang City - Gunawan, Gunawan (Jurnal Sosiologi USK (Media Pemikiran & Aplikasi), 2024)
Indonesias pluralistic society, characterized by its diverse religious communities, presents unique opportunities and challenges in fostering interfaith harmony. Nahdlatul Ulama (NU), as the largest Islamic organization in Indonesia, plays a vital role in bridging religious divides and promoting tolerance. This study examines NUs contributions in Palembang, a city known for its multicultural dynamics, through Pierre Bourdieus framework of social capital, focusing on how trust, social networks, and shared norms are utilized to sustain harmony among diverse groups. This qualitative study employs a descriptive approach, combining primary data from interviews with key informants and secondary data from relevant literature. Informants were selected based on their active involvement in NUs initiatives in Palembang, and data were analysed using the Miles and Huberman framework, which includes data reduction, data display, and conclusion drawing. The findings highlight six core activities undertaken by NU in fostering interfaith harmony: facilitating annual interfaith dialogues, promoting tolerance through educational institutions, engaging in inclusive social activities, advocating moderate Islamic teachings, influencing public policy, and implementing community empowerment programs. These efforts align with Bourdieus components of social capitaltrust, social networks, and shared normsserving as mechanisms to strengthen relationships and mitigate conflicts among religious groups. NUs strategies demonstrate the dynamic interplay between social capital and societal cohesion. The organization effectively mobilizes trust through collaborative efforts such as mutual cooperation in community projects. Its expansive social networks, encompassing grassroots groups and policymakers, amplify its impact, while shared norms of inclusivity and tolerance form the foundation of its habitus. Despite facing challenges such as resistance from conservative groups and structural inequalities, NU adapts by leveraging digital platforms and forming partnerships to sustain its initiatives.